Nutrition promotion: the role of monitoring physical growth - Zulkifli, S.N. (SAGE Publications, 1992)
Growth monitoring has been included as one of the basic strategies for child survival. In this paper, the rationale for this is reiterated both for individual as well as population nutritional surveillance. Methods for and approaches to growth monitoring are described. In addition, potential problems in implementing growth monitoring projects and interpreting the results are discussed. Despite its lack of sensitivity and specificity as a diagnostic tool, its advantages in terms of low cost, simplicity, reliability and social acceptability justify its use in nutritional surveillance, particularly in populations at risk of malnutrition.